Driven to distraction site-specific street sign appropriation - Vergara, Eunice; Abaya, Leo A.C. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2016)
Signs and symbols, when used to represent a concept or an idea, are powerful tools for communication to affect viewers. A common and significant kind of signs and symbols are street signs. Street signs are symbols that can be seen in our everyday lives. It has become a common sight for commuters, drivers, and pedestrians. In the Philippine context, street signs have already been part of the daily struggle of Filipinos due to heavy traffic. These street signs serve as a function for the movement of the people and traffic management. My daily transportation experiences and background research on street signs have inspired me to explore the deeper understanding and appreciation of street signs along with its powerful effect. My thesis is anchored on the inquiry, how can road signs be appropriated to a site-specific installation in order to create an engaging artwork regarding the University of the Philippines-Diliman life and culture? Specifically, my thesis work aimed to create an appropriated imagery of street signs about the university through site - specific installation, to create a diverse interpretation of the appropriated imagery of road signs, and locate an appropriate and saturated site for installation in order to maximize accessibility to viewers. To address the objectives, my thesis involved site-specific street signs installed in various zones of the university. Standards used on making of street signs (materials, size, shapes) are followed while the designed images are based on the context of the area where it is installed. My thesis is not intended for traffic management but for viewer's observation and reflection of the context behind site-specific street sign.
Thesis (Bachelor in Fine Arts (Painting))--University of the Philippines Diliman
Bibliography : leaves 51-52.
Keywords: Site-specific installations (Art); Street signs -- Philipppines -- Diliman (Quezon City); Symbolism in art